ANALISIS FAKTOR-FAKTOR PENENTU DALAM KEPUTUSAN PEMBELIAN IKAN KAKAP MERAH DI PT. MATSYARAJA ARNAWA STAMBHAPURA KOTA KUPANG (Jurnal Pembangunan Perikanan dan Agribisnis, 2025)
This study aims to identify the determinants of purchasing decisions for red snapper at PT Matsyaraja Arnawa Stambhapura. The type of research used in this study is quantitative. The population involved in this study were consumers who had bought red snapper more than once. The sampling technique in this study was accidental sampling. Determination of the number of samples in the study was 50 respondents. The data analysis used is multiple linear regression. The findings show that based on the results of the study, the conclusions in this study, namely 1). The variables of price, product quality, preference, location, promotion, and purchasing decisions have a positive and significant influence together on fish purchasing decisions at PT. Matsyaraja Arnawa Stambhapura, Kupang City. 2). The variables of price, product quality, preference, location, promotion, and purchasing decisions have a positive and significant influence individually on fish purchasing decisions at PT. Matsyaraja Arnawa Stambhapura, Kupang City with the amount of influence in order (26,9%; 13,1%; 20,8%; 36,5%; 10,7%).